A Double Inertial Mann-Type Method for Two Nonexpansive Mappings with Application to Urinary Tract Infection Diagnosis - Krittin Naravejsakul; Pasa Sukson; Waragunt Waratamrongpatai; Phatcharapon Udomluck; Mallika Khwanmuang; Watcharaporn Cholamjiak; Watcharapon Yajai (Mathematics)
This study proposes a double inertial technique integrated with the Mann algorithm to address the fixed-point problem. Our method is further employed to tackle the split-equilibrium problem and perform classification using a urinary tract infection dataset in practical scenarios. The Extreme Learning Machine (ELM) model is utilized to categorize urinary tract infection cases based on both clinical and demographic features. It exhibits excellent precision and efficiency in differentiating infected from non-infected individuals. The results validate that the ELM provides a rapid and reliable method for handling classification tasks related to urinary tract infections.